Linking Cooperative Health Insurance Service Characteristics to Expatriates' Satisfaction: Mediating Role of Customer Knowledge - Mubarak Aldosari; Yusnidah Ibrahim; Norlida Binti Abdul Manab; Ebrahim Mohammed Al-Matari; Eqab Aiyadh Alotaibi (International Review of Management and Marketing, 2016)
Extant empirical research has established a significant and positive relationship between Cooperative Health Insurance (CHI) service characteristics and expatriates' satisfaction. The present study investigated the psychological mechanism underlying these relationships by incorporating customer knowledge as a mediating variable. A self-report survey-based was used to collect data from 384 expatriates employed by both service and manufacturing organizations located in five main regions of Saudi Arabia, representing Central region, the Eastern region, the Western region, the Northern region and the Southern region. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), we found a significant positive relationship between availability of CHI service is positively related to expatriates' satisfaction. Similarly, the results indicated that perceived service quality of CHI had a significant positive relationship with expatriates' satisfaction.  As expected, customer knowledge was found to mediate the relationship between availability of CHI service and expatriates' satisfaction.  In addition, we also found customer knowledge to be a significant mediating variable between perceived service quality of CHI and expatriates' satisfaction.  Implications of the study in the Saudi Arabian context have been discussed.